KERAGAMAN SPESIES HERBA DAN KEMIRIPAN KOMUNITAS TUMBUHAN PADA DUA PERIODE PEMANTAUAN BERURUTAN DI AREA REKLAMASI PT ADARO INDONESIA, PROVINSI KALIMANTAN SELATAN, INDONESIA - Yoga Bayu Santoso; Mochamad Arief Soendjoto; Daniel Itta; Fazlul Wahyudi (Jurnal Sylva Scienteae, 2021)
The development of herbaceous species according to the time of monitoring at certain sample locations in the PT Adaro Indonesia reclamation area has never been published. The purpose of the study was to compare the diversity of species and the similarity of plant communities growing in certain locations in two consecutive monitoring periods. Four locations that have been revegetated were sampled. At each location, 13 measuring plots (20 m x 20 m) were made and placed systematically. In each of these plots, 2 sub-plots (5 m x 5 m) were placed in 2 angles in opposite positions. From each sub-plot data in the form of herbaceous species names and number of individuals were collected. In one location, the number of plots changed because part of this location turned out to be active mining areas. The number of remaining plots (6 plots) was considered to not affect the results. Data is processed to obtain the density of each species at a certain location (Ki), the relative density of certain species (KRi), the frequency of each species at a certain location (Fi), the relative frequency of certain species (FRi), the importance value index (IVI), the index of species diversity Shannon-Wienner (H'), and the similarity index of the Dice community (IS). The number of species varies at each sample location and shows an increase from first monitoring to second monitoring. The species diversity index also increases. Community similarity index varies, both with calculations based on the presence or absence of species and based on the IVI. Both methods of calculation can be used but it is recommended to use calculations based on IVI.Keywords: Diversity, Monitoring period, Reclamation area, Similarity